PENGARUH PAJAK PENGHASILAN, KEPEMILIKAN ASING, LEVERAGE, DAN KUALITAS KAP TERHADAP TRANSFER PRICING (Studi Empiris Perusahaan Sektor Pertambangan Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2017-2019) - , Eka Hariyani, Rizka Amilia , Vince Ratnawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Transfer pricing was originally known in the field of management accounting as a pricing policy applied to the delivery of goods or services between departments with the aim of measuring the performance of each of these divisions or departments. Conceptually, transfer pricing can be applied for three different purposes. First, from a company legal standpoint, transfer pricing can be used as a tool to increase efficiency and synergy between the company and its shareholders. This research is to analyze the effect of tax, foreign ownership, leverage and cap quality on transfer pricing (Empirical Study of Mining Sector Companies Listed on the Indonesia Stock Exchange in 2017-2019). The population in this study are mining sector companies listed on the Indonesia Stock Exchange in 2017-2019. The sample selection was based on the purposive sampling method, namely sampling based on the subjective considerations of the researchers so that the total sample became 78 samples from 26 companies multiplied by 3 years using multiple linear regression analysis. The results in this study indicate that taxes, foreign ownership and leverage have a significant positive effect on corporate transfer pricing. Meanwhile, KAP quality has no significant effect on transfer pricing decisions. This shows that companies audited by KAP have a lot of knowledge about how to detect and can manipulate financial statements that may be carried out by companies so that they do not guarantee that KAPs that have a good reputation will not commit fraudulent transfer pricing practices.